Determination of the most susceptible phenological stage of rice panicles to infection by species of Fusarium graminearum - Scheidt,Bruno Tabarelli (2019)
ABSTRACT Occurrence of rice seeds infected by Fusarium graminearum has shown the importance of identifying the most favorable phenological stage of panicles to grain infection. The experiments were conducted in two crop seasons under greenhouse conditions, using the rice hybrid INOV CL. The phenological stages during inoculation were complete booting, full heading and flowering. All plots were inoculated using two isolates of Fusarium graminearium species complex 15A (F. graminearium - 15-ADON) and FmNiv (F. meridionale - Nivalenol). Disease severity was estimated at weekly intervals and was used to calculate the area under the disease progress curve (AUDPC), while panicles were collected to determine the percentage of spotted grains and Fusarium incidence. Percentage of spotted grains and incidence of F. graminearum and F. meridionale were greater when inoculation was made during flowering stage, significantly differing from heading and booting stages. Rice flowering stage is more susceptible to infection by F. graminearum and F. meridionale, inducing higher disease severity and incidence of spotted grains, as well as presence of fungi in the grains. Flowering was the most susceptible stage in the two crop seasons for both isolates, and the complete booting stage presented the lowest values of AUDPC.